Organización Contable a la Empresa de Celulares El Churón, de la Ciudad de Loja, periodo Enero – Marzo del 2016 - Jiménez Abad, Verónica Matilde (2017)
This dissertation entitled: "ACCOUNTING ORGANIZATION TO THE CELLULAR COMPANY OF THE CITY OF THE SHOP CITY, PERIOD JANUARY - MARCH 2016.", aims to propose an accounting organization that allows its owner to know in a timely manner real economic and financial situation of the business, and in this way make the right decisions and improvement. For this, the objectives set out in the thesis project were fulfilled through the development and application of the accounting process, starting with the elaboration of an account plan and manual, which allows for ordering the accounts of assets, liabilities, equity, costs and expenses; Being necessary to make an analysis of the economic activity that is part of the company and in turn the observation of the source documentation that uses the same, to be able to determine the accounting accounts and the codes to use, then with the chart of accounts the manual is elaborated Of accounts with an explanation of each of the accounts and sub-accounts for the chronological development of the accounting process. Subsequently, the initial inventory was carried out to determine all assets, rights and obligations of the company; Making the physical count of each of the articles and values that the company has and thus obtaining the initial state of the situation, in which the accounts that own the asset, liability and equity are detailed, resulting in 7 a capital of $ 35,464.54 with which it counts the commercial premises for the development of its activities. In addition, ancillary records of sales, purchases, payment roles and provisions were made, by means of weekly registration in the case of sales and in purchases, the auxiliary was performed on a daily basis, the role of payments where all income As well as their respective deductions was made from the three months January, February and March, the calculation of said provisions was developed as the thirteenth, fourteenth and reserve fund to be used in the different transactions of the daily book And which serves as the basis for establishing the financial statements. Finally, the accounting process was elaborated through the permanent inventory control system until obtaining the Financial Statements in order to know the real economic-financial situation of the company, starting with the Initial Inventory, the Initial Situation Statement, the Daily Book , General Ledger, Check Balance, Worksheet and Financial Statements such as: the Income Statement where the net income for the year was determined with a value of $ 443.13 this result is obtained from the difference of income and expenses during the period; In the Statement of Financial Position, the assets with a value of $ 38,275.73 are reflected, while in liabilities there is a total of $ 2,289.86, with a capital of $ 35,985.87 in the three months analyzed. Finally, the Statement of Cash Flow The same one that 8 synthesizes the income and expenses of the monetary resources, that is to say the movements of the cash account and banks, to the same Financial Statements was realized the application of the Financial Ratios such as: the reasons of liquidity; Where we can say that the company has a liquidity favorable to fulfill its obligations in the short term, with a satisfactory working capital to continue with the normal turnover of the business; As to the activity ratios by applying the inventory rotation and the total asset turnover indicates that the result is low due to the amount of inventory stored; The level of indebtedness of the business is little relevant since the majority of its capital has been financed from the resources of the owner; In the profitability of the business was obtained a very insignificant result since the margin of profit of the business is low because its expenses are high and for that it should have much more sales. The methodology used in this dissertation work is the application of the permanent account inventory system, which allowed control of the goods through the kdedex cards that allow to determine the merchandise in existence and the cost of the same. The most relevant conclusion is that the owner of the company will have accurate and timely information on the progress of the business through the accounting process and the establishment of the financial statements as the Income Statement that determines the profit or loss for the year, the State of Financial Situation shows what the company has in assets, liabilities and equity and the Statement of Cash Flow determines the income and expenses of cash, based on these results that the company can organize and control its resources effectively and make more profits.